Market-based approaches to environmental management: A review of lessons from payment for environmental services in Asia - Bhim Adhikari (Asian Development Bank Institute (ADBI), 2009)
Market-based approaches to environmental management, such as payment for environmental services (PES), have attracted unprecedented attention during the past decade. PES policies, in particular, have emerged to realign private and social benefits such as internalizing ecological externalities and diversifying sources of conservation funding as well as making conservation an attractive land-use paradigm. In this paper, we review several case studies from Asia on payment for environmental services to understand how landowners decide to participate in PES schemes. The analysis demonstrates the significance of four major elements facilitating the adoption and implementation of PES schemes: property rights and tenure security, transaction costs, household and community characteristics, communications, and the availability of PES-related information. PES schemes should target win-win options through intervention in these areas, aimed at maintaining the provision of ecological services and improving the conditions for local inhabitants.
Keywords: Q57; 330